2023
DOI: 10.1021/acsapm.3c00168
|View full text |Cite
|
Sign up to set email alerts
|

Photoiniferter RAFT Polymerization of Optically Active Hydrophilic Vitamin B5 Analogous Methacrylamide

Abstract: Chiroptical polymers are interesting due to diverse applications in the field of chromatography, biomedicines, and catalysis. This study describes the synthesis of new types of optically active polymers of vitamin B5 analogous methacrylamide (B5AMA) using a photoiniferter polymerization approach at ambient temperatures. Enantiomers of B5AMA monomer ((R) and (S)) were prepared by the ring opening method and were characterized for their optical activity. The monomers were then polymerized by a photoiniferter pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…2-Aminoethylmethacrylamide hydrochloride (AEMA) and vitamin B5 analogous methacrylamide (B5AMA) monomers were synthesized according to previously reported procedures and were analyzed using 1 H NMR and 13 C NMR (Supporting Information Figure S1). Di­(ethylene glycol) methyl ether methacrylate (DEGMEM, 95%, Sigma-Aldrich) was passed through a small column packed with silica to remove the inhibitors contained in the reagents. 3,9-Divinyl-2,4,8,10-tetraoxaspiro[5.5]­undecane (OXAS, 98%, Sigma-Aldrich), potassium persulfate (95%, Sigma-Aldrich), 2,2'-Azobis­[2-(2-imidazolin-2-yl)­propane] Dihydrochloride (VA-044, 98%, TCI).N , N , N ′, N ′-tetramethylethylenediamine (99%, Thermo Scientific), (5-carboxytetramethylrhodamine) (TAMRA, Fisher Scientific), 4,4′-azobis­(4-cyanovaleric acid) (ACVA, 98%, Sigma-Aldrich), phosphotungstic acid (PTA, Sigma-Aldrich), 4-morpholinoethanesulfonic acid (MES monohydrate, >98.5%, Fisher), 1-ethyl-3-(3-(dimethylamino)­propyl)­carbodiimide hydrochloride (EDC, Thermo), N -hydroxysuccinimide (NHS, Thermo), 4-((((2-carboxyethyl)­thio)­carbonothioyl)­thio)-4-cyanopentanoic acid (CTA, 95%, Sigma-Aldrich), and absolute ethanol (Les Alcools de Commerce) were used as received.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2-Aminoethylmethacrylamide hydrochloride (AEMA) and vitamin B5 analogous methacrylamide (B5AMA) monomers were synthesized according to previously reported procedures and were analyzed using 1 H NMR and 13 C NMR (Supporting Information Figure S1). Di­(ethylene glycol) methyl ether methacrylate (DEGMEM, 95%, Sigma-Aldrich) was passed through a small column packed with silica to remove the inhibitors contained in the reagents. 3,9-Divinyl-2,4,8,10-tetraoxaspiro[5.5]­undecane (OXAS, 98%, Sigma-Aldrich), potassium persulfate (95%, Sigma-Aldrich), 2,2'-Azobis­[2-(2-imidazolin-2-yl)­propane] Dihydrochloride (VA-044, 98%, TCI).N , N , N ′, N ′-tetramethylethylenediamine (99%, Thermo Scientific), (5-carboxytetramethylrhodamine) (TAMRA, Fisher Scientific), 4,4′-azobis­(4-cyanovaleric acid) (ACVA, 98%, Sigma-Aldrich), phosphotungstic acid (PTA, Sigma-Aldrich), 4-morpholinoethanesulfonic acid (MES monohydrate, >98.5%, Fisher), 1-ethyl-3-(3-(dimethylamino)­propyl)­carbodiimide hydrochloride (EDC, Thermo), N -hydroxysuccinimide (NHS, Thermo), 4-((((2-carboxyethyl)­thio)­carbonothioyl)­thio)-4-cyanopentanoic acid (CTA, 95%, Sigma-Aldrich), and absolute ethanol (Les Alcools de Commerce) were used as received.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we explore the synthesis, IRI activities, and cryopreservation efficacies of vitamin B5- analogous methacrylamide (B5AMA) nanogels, and their cryogenic behavior is compared with the linear poly­(B5AMA). The highly hydrophilic macromolecules of B5AMA are recently reported for water adsorption and release, for antifouling behavior, and for salt-responsive properties, owing to the hydrogen bonding capabilities of poly­(B5AMA) chains with water molecules. Given the hygroscopic behavior of poly­(B5AMA) and their hydrogels, poly­(B5AMA) nanogels hold significant potential as CPA for microbial and mammalian cell storage.…”
Section: Introductionmentioning
confidence: 99%
“…4-[[[(2-carboxyethyl) thio] thioxomethyl] thio]-4-cyano-pentanoic acid (TCT-1, 95%, Sigma-Aldrich, Oakville, ON, Canada), 3-(trimethylsilyl)-1-propanesulfonic acid sodium salt (TMSP, 97%, Sigma-Aldrich, Oakville, Canada), methanol (99.9%, Fisher, Ottawa, Canada), N,N-dimethylformamide (DMF, 99.9%, Sigma-Aldrich, Oakville, ON, Canada), ( R )-pantolactone (99%, Sigma-Aldrich, Oakville, Canada), ( S )-pantolactone (97%, Ambeed, IL, USA), deuterium oxide (99%, Cambridge Isotope Laboratories Inc., Quebec, QC, Canada), poly(ethylene glycol) methyl ether) (PEG, MN of 10000, Sigma-Aldrich, Oakville, ON, Canada), bovine serum albumin (BSA, 98%, Sigma-Aldrich, Oakville, Canada), lysozyme (LYZ, Biobasic Canada, Markham, ON, Canada), phosphate-buffered saline tablets (Millipore-Sigma, Burlington, MA, USA), and chloroform-d (99.8%, Sigma-Aldrich, Oakville, ON, Canada) were used as received. Vitamin B5 analogous methacrylamide R -(+)- and S -(−)-B5AMA monomers were synthesized according to a previously reported procedure [ 30 ] and analyzed using 1 H NMR and 13 C NMR ( Figures S1–S4 ).…”
Section: Methodsmentioning
confidence: 99%
“…We have recently reported the synthesis of biomimetic polymers of vitamin B5 analogous methacrylamide (B5AMA) through a living radical polymerization approach and have shown that the poly(B5AMA) produced is highly hydrophilic and exhibits antifouling properties when grafted on a solid support [ 28 , 29 , 30 , 31 ]. Owing to the strong hydration tendency, poly(B5AMA) of different molecular weights exhibited the depletion aggregation of bacteria [ 29 ], and surface-tethered poly(B5AMA) chains showed low fouling behaviour for both proteins and bacteria [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation